2022
DOI: 10.1093/cid/ciac860
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for Prosthetic Valve Endocarditis: Impact of Molecular Imaging by FISHseq Diagnostics

Abstract: Background The causative microbial etiology of prosthetic valve infective endocarditis (PVE) can be difficult to identify. Our aim was to investigate the benefit of the molecular imaging technique fluorescence in situ hybridization (FISH) combined with 16S rRNA-gene PCR and sequencing (FISHseq) for the analysis of infected prosthetic heart valves. Methods We retrospectively evaluated the diagnostic outcome of 113 prosthetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…For patients with prosthetic valve BCNIE, molecular imaging technique fluorescence in situ hybridization combined with 16S rRNA-gene PCR and sequencing improved the conventional cultural diagnostic methods in 30% of cases. 159 Next-generation sequencing of plasma microbial cell-free deoxyribonucleic acid (DNA) may facilitate a rapid diagnosis of IE in the future. 160 When all microbiological assays are negative, the diagnosis of nonbacterial endocarditis should systematically be considered and assays for antinuclear antibodies as well as antiphospholipid syndrome (APLs) (anticardiolipin antibodies [immunoglobulin (Ig)G] and anti-β 2 -glycoprotein 1 antibodies [IgG and IgM]) should be performed (although these antibodies may also be present in patients with proven IE).…”
Section: Blood Culture-negative Infective Endocarditismentioning
confidence: 99%
“…For patients with prosthetic valve BCNIE, molecular imaging technique fluorescence in situ hybridization combined with 16S rRNA-gene PCR and sequencing improved the conventional cultural diagnostic methods in 30% of cases. 159 Next-generation sequencing of plasma microbial cell-free deoxyribonucleic acid (DNA) may facilitate a rapid diagnosis of IE in the future. 160 When all microbiological assays are negative, the diagnosis of nonbacterial endocarditis should systematically be considered and assays for antinuclear antibodies as well as antiphospholipid syndrome (APLs) (anticardiolipin antibodies [immunoglobulin (Ig)G] and anti-β 2 -glycoprotein 1 antibodies [IgG and IgM]) should be performed (although these antibodies may also be present in patients with proven IE).…”
Section: Blood Culture-negative Infective Endocarditismentioning
confidence: 99%
“…It is also detected in the general population as an asymptomatic pathogen. A study reported its incidence to be 3 in a million, and no relevant epidemiological report from China exists[ 13 ]. It is primarily manifested with intermittent and recurrent arthralgia or arthritis with chronic diarrhea, abdominal pain, and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Tiêu chuẩn Duke-ISCVID 2023 đã làm rõ và mở rộng tiêu chuẩn này bởi phối hợp các kĩ thuật di truyền, phân tử, nhuộm mô ở đó vi sinh vật gây bệnh có thể được phát hiện (bảng 1). Đa dạng các cận lâm sàng chẩn đoán mới, bao gồm PCR 16S/18S rRNA, kĩ thuật giải trình tự gen 9 , và lai huỳnh quang tại chỗ 10 , có thể tăng khả năng của chúng ta cho chẩn đoán VNTMNK. e Xác định chẩn đoán thay thế giải thích triệu chứng cơ năng và thực thể của VNTMNK bao gồm nguyên nhân vi sinh và không phải vi sinh.…”
Section: Tiếp Cận Chẩn đOán Chẩn đOán Xác địNh Vntmnk Dựa Trên Tiêu C...unclassified